Ongoing measles outbreak in Greece related to the recent European-wide epidemic. Issue 13 (8th August 2018) - Georgakopoulou, T.; Horefti, E.; Vernardaki, A.; Pogka, V.; Gkolfinopoulou, K.; Triantafyllou, E.; Tsiodras, S.; Theodoridou, M.; Mentis, A.; Panagiotopoulos, T.
Abstract: We report an ongoing measles outbreak in Greece. The first cases were notified through the mandatory notification system on May 2017 in Northern Greece and concerned a cluster of three imported cases in unvaccinated Roma siblings. So far, 3150 cases have been reported in all 13 Regions. Initially, the outbreak mainly affected Greek Roma but as it progressed it spread to non-minority Greek nationals. The outbreak reached its ultimate peak on week 10/2018 but from week 15/2018 has been gradually declining. Most cases (60.6%) were Roma (especially children <10 year-old) followed by non-minority Greek nationals (29.3%; mostly young adults). The majority (80.4%) were unvaccinated. Interestingly, 129 (4.1%) cases were healthcare workers (HCWs). Genotype B3 was identified by molecular methods in all 87 cases tested. Overall, 61.3% of the cases were hospitalised. Complications were reported in 17.1% of the cases among which four deaths. The outbreak occurred after 3 years without local endemic measles transmission. Extensive vaccination implemented as the major public health measure managed to prevent the emergence of a large number of cases in refugee/migrant hosting sites. Mitigation efforts currently focus on raising awareness among HCWs and closing the immunisation gap in populations with suboptimal vaccination coverage.